How do late terminations of pregnancy affect comparisons of stillbirth rates in Europe? Analyses of aggregated routine data from the Euro‐Peristat Project. (17th July 2017) - Blondel, B; Cuttini, M; Hindori‐Mohangoo, AD; Gissler, M; Loghi, M; Prunet, C; Heino, A; Smith, L; van der Pal‐de Bruin, K; Macfarlane, A; Zeitlin, J; ,
Abstract : Objective: To describe how terminations of pregnancy at gestational ages at or above the limit for stillbirth registration are recorded in routine statistics and to assess their impact on comparability of stillbirth rates in Europe. Design: Analysis of aggregated data from the Euro‐Peristat project. Setting: Twenty‐nine European countries. Population: Births and late terminations in 2010. Methods: Assessment of terminations as a proportion of stillbirths and derivation of stillbirth rates including and excluding terminations. Main outcome measures: Stillbirth rates overall and excluding terminations. Results: In 23 countries, it is possible to assess the contribution of terminations to stillbirth rates either because terminations are rare occurrences or because they can be distinguished from spontaneous stillbirths. Where terminations were reported, they accounted for less than 1.5% of stillbirths at 22+ weeks in Denmark, between 13 and 22% in Germany, Italy, Hungary, Finland and Switzerland, and 39% in France. Proportions were much lower at 24+ weeks, with the exception of Switzerland (7.4%) and France (39.2%). Conclusions: Terminations represent a substantial proportion of stillbirths at 22+ weeks of gestation in some countries. Countries where terminations occur at 22+ weeks should publish rates with and without terminations in order to improve international comparisons and the policy relevance of stillbirth statistics. Tweetable abstract: For valid comparisons of stillbirth rates, data about late terminations of pregnancy are needed. Plain Language Summary: To compare stillbirth rates across countries, it is important to have uniform rules for registering and reporting these deaths. In Europe, stillbirth statistics include babies who die before birth and are delivered starting at 22 weeks of gestation, although a cut‐off of 24 weeks is used in some countries, such as the UK. One factor affecting the comparability of stillbirth statistics is whether they include spontaneous deaths as well as those after a medical termination of pregnancy because of major fetal defects or severe maternal complications. Regulations and reporting practices for terminations in late pregnancy vary between countries and may have a substantial effect on national stillbirth statistics. Our first objective was to determine if terminations of pregnancy at or after 22 weeks are included in routine stillbirth statistics in 29 European countries participating in the Euro‐Peristat project (http://www.europeristat.com ). In 15 countries, terminations were rarely carried out after the registration cut‐off (estimated at fewer than 4% of stillbirths). In another 8 countries, pregnancy terminations were reported and could be distinguished from spontaneous stillbirths. Our first conclusion is that the contribution of terminations to stillbirths is known in most European countries, with a few exceptions. Our second objective was to examine the impact of terminations on stillbirth rates in Europe using routine statistics. In six countries, terminations account for over 10% of stillbirths at 22 weeks and beyond. At 24 weeks or beyond, terminations accounted for fewer than 5% of stillbirths, except in Switzerland (7%) and France (39%). Our second conclusion is that terminations can strongly affect some countries' stillbirth rates, especially when rates are reported for births at 22 or more weeks. Based on these results, we recommend that European stillbirth rates be reported overall and excluding terminations in order to improve the comparability of stillbirth rates between countries. Tweetable abstract: For valid comparisons of stillbirth rates, data about late terminations of pregnancy are needed.